2013
DOI: 10.1088/0029-5515/53/8/083026
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic properties and active magnetic topology modification in the RFX-mod edge plasma

Abstract: A better understanding of the edge phenomena regulating plasma transport and turbulence is of primary importance for the whole fusion community. In particular, in reversed field pinches (RFPs) the edge properties are found to have a strong relation with the magnetic topology. The flexibility of the RFX-mod RFP experiment (Sonato et al 2003 Fusion Eng. Des. 66–68 161–8) enables exploring different topological regimes, and the insertion of a probe equipped with a two-dimensional array of electrostatic sensors al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 62 publications
4
11
0
Order By: Relevance
“…The convective term v ϕ L n in the RFP can be two orders of magnitude larger than the diffusive term, as it has been shown elsewhere [21]. In RFX low current discharges, it is possible to measure also the radial component of the flow, v r , with insertable probes (even if in a different symmetry, the helical 1/7), thus confirming the presence of a convective cell, dragging plasma along the helical angle [57,58]. E × B convective cells have been measured around edge-resonant islands in tokamaks and stellarators [59][60][61][62] and provide an interesting link between the density limit and experiments with RMPs.…”
Section: Plasma Flow and Marfesupporting
confidence: 53%
“…The convective term v ϕ L n in the RFP can be two orders of magnitude larger than the diffusive term, as it has been shown elsewhere [21]. In RFX low current discharges, it is possible to measure also the radial component of the flow, v r , with insertable probes (even if in a different symmetry, the helical 1/7), thus confirming the presence of a convective cell, dragging plasma along the helical angle [57,58]. E × B convective cells have been measured around edge-resonant islands in tokamaks and stellarators [59][60][61][62] and provide an interesting link between the density limit and experiments with RMPs.…”
Section: Plasma Flow and Marfesupporting
confidence: 53%
“…A major difference between these two zones, inside and outside the LCFS, regards the presence of LRC. Recent experiments showed that the presence of LRCs in RFX-mod can be detected only when the region internal to the m = 0 islands is explored [42]: this can be expected recalling that in tokamaks LRCs are observed entering the separatrix. It is worth considering that these measurements of LRCs regard low current (I p ∼ 450 kA) MH discharges, hence they cannot be read as a proof of a more general existence of LRCs in the confined RFP plasma.…”
Section: Electron Temperature and Energy Confinementmentioning
confidence: 83%
“…By evaluating the crosscorrelation between toroidally spaced floating potential probes it is possible to obtain an estimate of the propagation velocity of V f fluctuations; since the probes are also installed at different poloidal angles, ( ) θ φ v t, is evaluated. In previous papers [10,29,30] it was observed that the spatial structure of φ v reflects the magnetic field topology, but detailed analyses along the poloidal direction are missing. Here we show in figure 12 the fluctuation of the toroidal velocity δ = − φ φ φ v v v as a function of the helical angle for four different poloidal angles.…”
Section: D Edge Perpendicular Velocitymentioning
confidence: 99%